Analisis Pengendalian Kualitas Produk Stik Bawang Putih Menggunakan Metode Statistical Quality Control (SQC) pada UMKM CR2FOOD di Kabupaten Sijunjung - Cantika Buswir, Amille; Dewantara, Masgar; Lusiana, Lusiana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the quality control of garlic stick products at CR2FOOD MSME in Sijunjung Regency using the Statistical Quality Control (SQC) method. The research employed a quantitative descriptive approach. Research data were obtained through direct observation of the production process, interviews with the business owner, and documentation of production data. Data analysis was conducted using quality control tools within the SQC method, including check sheets, Pareto diagrams, cause-and-effect diagrams (fishbone diagrams), and control charts. The results of the study indicate that several types of product defects are still found, namely non-uniform stick shapes, excessively hard product texture, and uneven levels of doneness. Based on the Pareto diagram analysis, the most dominant defect is the non-uniform shape of the sticks. The fishbone diagram analysis shows that the main causes of defects originate from human factors, production methods, raw materials, and equipment. Therefore, improvements in the production process are required through the implementation of standard operating procedures (SOP), enhancement of workers’ skills, and stricter quality supervision to ensure consistent product quality.